Optimal and actual rates of Stereotactic Ablative Body Radiotherapy (SABR) utilisation for primary lung cancer in Australia. (May 2022) - Ghandourh, Wsam; Holloway, Lois; Batumalai, Vikneswary; Chlap, Phillip; Field, Matthew; Jacob, Susannah
Highlights: Stereotactic Ablative Body Radiotherapy (SABR) plays a major role in the management of early-stage non-small cell lung cancer (NSCLC). An evidence-based model is developed to estimate optimal rates of lung SABR utilisation within the Australian population. Optimal utilisation rates are compared against actual utilisation rates to evaluate service provision. Abstract: Background and purpose: Radiotherapy utilisation rates considerably vary across different countries and service providers, highlighting the need to establish reliable benchmarks against which utilisation rates can be assessed. Here, optimal utilisation rates of Stereotactic Ablative Body Radiotherapy (SABR) for lung cancer are estimated and compared against actual utilisation rates to identify potential shortfalls in service provision. Materials and Methods: An evidence-based optimal utilisation model was constructed after reviewing practice guidelines and identifying indications for lung SABR based on the best available evidence. The proportions of patients likely to develop each indication were obtained, whenever possible, from Australian population-based studies. Sensitivity analysis was performed to account for variations in epidemiological data. Practice pattern studies were reviewed to obtain actual utilisation rates. Results: A total of 6% of all lung cancer patients were estimated to optimally require SABR at least once during the course of their illness (95% CI: 4–6%). Optimal utilisation rates were estimated to be 32% for stage I and 10% for stage II NSCLC. Actual utilisation rates for stage I NSCLC varied between 6 and 20%. For patients with inoperable stage I, 27–74% received SABR compared to the estimated optimal rate of 82%. Conclusion: The estimated optimal SABR utilisation rates for lung cancer can serve as useful benchmarks to highlight gaps in service delivery and help plan for more adequate and efficient provision of care. The model can be easily modified to determine optimal utilisation rates in other populations or updated to reflect any changes in practice guidelines or epidemiological data.